2013 IEEE Intelligent Vehicles Symposium (IV) 2013
DOI: 10.1109/ivs.2013.6629465
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of trajectory tracking controllers for emergency situations

Abstract: Over the last years a number of different vehicle controllers has been proposed for tracking planned paths or trajectories. Most of previously published works do not compare their results with other approaches or limit the comparison to a few scenarios. Unfortunately, comparisons with existing controller concepts are very rare and a ranking is hard to establish from the literature. In this work, we rigorously compare inversion-based trajectory tracking controllers by systematically exploring the set of possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…The results presented in this work build upon and greatly extend those of [11,12]. The extension is so great that several arguments can be proposed as a result of the observations detailed in Section 3.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The results presented in this work build upon and greatly extend those of [11,12]. The extension is so great that several arguments can be proposed as a result of the observations detailed in Section 3.…”
Section: Introductionsupporting
confidence: 73%
“…Research similar to this study can be found in [11,12], which uses a single lane change and a double lane change maneuver to evaluate a set of lateral motion controllers. They study the performance under nominal, model discrepancies, low friction, and sensor noise disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…1, ➃). Candidates for trajectory tracking controllers for emergency maneuvers are evaluated in a previous work [26].…”
Section: Basic Ideamentioning
confidence: 99%
“…However, these studies did not reflect the performance of controllers in real-world situations with unexpected disturbances. In [33], the authors compared trajectory tracking controllers under disturbances and sensor noise, but they only reported the comparison of two flatness-based controllers.…”
Section: Introductionmentioning
confidence: 99%